Evaluation of Surface Slope Irregularity in Linear Parabolic Solar Collectors - F. Francini; D. Fontani; P. Sansoni; L. Mercatelli; D. Jafrancesco; E. Sani (International Journal of Photoenergy)
The paper describes a methodology, very simple in its application, for measuring surface irregularities of linear parabolic collectors. This technique was principally developed to be applied in cases where it is difficult to use cumbersome instruments and to facilitate logistic management. The instruments to be employed are a digital camera and a grating. If the reflector surface is defective, the image of the grating, reflected on the solar collector, appears distorted. Analyzing the reflected image, we can obtain the local slope of the defective surface. These profilometric tests are useful to identify and monitor the mirror portions under mechanical stress and to estimate the losses caused by the light rays deflected outside the absorber.